Implementation of some strategies of military, economic, and political support discourses analysis for Ukraine until 2025: arguments and counterarguments - Semenenko, Oleh; Abramova, Maryna; Onofriichuk, Vitalii; Kravchenko, Yevhen; Hetman, Alevtyna; Remez, Artem (Social Development and Security, 2023)
Purpose: the purpose of the article is to present views on the consequences of implementing some strategies of military, economic and political support for Ukraine until 2025, supported by the results of an expert survey. The article focuses on the analysis of the arguments and counterarguments of the respective analyzed positions of experts. Method: the main research methods are: analysis; synthesis; comparison; formalization and evaluation of the material. Findings: to highlight some of the current scientific and practical strategies for restoring Ukraine through its military, economic, and political support until 2025; to consider the possible results of their implementation from two perspectives (arguments for and against); to obtain a scientific justification for the possible effectiveness of these strategies until 2025, taking into account the results of the relevant expert survey. Theoretical implications is to convey to a wide range of scholars the specifics of the implementation of existing military, economic, and political support strategies as part of the Post-War Reconstruction Plan of Ukraine - possible positive and negative consequences of the impact on the country’s economy. Paper type: theoretical, descriptive, practical.